Protecting Forests From Conversion: The Essential Role of Supply-Side National Laws - Haywood, Caroline; Henriot, Clotilde (Frontiers in Forests and Global Change, 2019)
The growing demand in global markets for commodities like palm oil, soy and cocoa has a disastrous impact on forests, carbon emissions, as well as the lands and livelihoods of forest-dependent people. Governments, private sector, civil society and forest-dependent people have, separately or jointly, committed to voluntary actions to protect forests (e.g., pledges, zero deforestation commitments, certification standards). However, recent research shows that these voluntary commitments and standards have neither halted nor slowed deforestation. This demonstrates that they cannot stand alone. Alongside voluntary action, national legal frameworks that regulate forest conversion are crucial. This research explores the importance of national laws for reducing deforestation from forest-risk commodities and the legal options available to national law-makers to address competing demands for forested lands.